Answer:
![\large\boxed{y+1=3(x-1)}\\\\\boxed{y=3x-4}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7By%2B1%3D3%28x-1%29%7D%5C%5C%5C%5C%5Cboxed%7By%3D3x-4%7D)
Step-by-step explanation:
The point-slope form of an equation of a line:
![y-y_1=m(x-x_1)](https://tex.z-dn.net/?f=y-y_1%3Dm%28x-x_1%29)
<em>m</em><em> - slope</em>
<em>(x₁, y₁)</em><em> - a point on a line</em>
We have
![m=3,\ (1,\ -1)\to x_1=1,\ y_1=-1](https://tex.z-dn.net/?f=m%3D3%2C%5C%20%281%2C%5C%20-1%29%5Cto%20x_1%3D1%2C%5C%20y_1%3D-1)
Substitute:
![y-(-1)=3(x-1)\\\\\boxed{y+1=3(x-1)}](https://tex.z-dn.net/?f=y-%28-1%29%3D3%28x-1%29%5C%5C%5C%5C%5Cboxed%7By%2B1%3D3%28x-1%29%7D)
Convert to the slope-intercept form
![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
<em>m</em><em> - slope</em>
<em>b</em><em> - y-intercept</em>
<em>use the distributive property</em>
<em>subtract 1 from both sides</em>
![\boxed{y=3x-4}](https://tex.z-dn.net/?f=%5Cboxed%7By%3D3x-4%7D)